Model Efisiensi Pasar: Sebuah Studi Pengaruh Musiman Terhadap Volume Perdagangan Saham Di BEI Emiten Lq 45 Tahun 2010-2013 - Zul Azmi; Wenni Hasmita (Journal Development, 2016)
The objective of this research is to empirically re-examine the influence of seasonal anomaly or calendar effect in financial markets called the Monday effect, week-four effect and Rogalski effect to stock trading volumein Indonesia Stock Exchange.The sample is selected using purposive sampling Technique, the sample consist of twenty four active stock in LQ 45 index during January 2010 through December 2013. The statistic methods which used to test the hypotesis are Analysis of Variance (ANOVA) and Independent Sample t-test. The results of this study indicate that there is the day of the week effect in IDX. The finding shows that there are different stock trading volume for five trading days. The highest and the lowest volume are observed on Wednesday and Monday. Analysis of week-four effect in IDX does not find the existance of this phenomenon in IDX, this paper shows the Monday effect accurs not only in the fourth week but olso in the first three weeks. Further test shows that Rogalski effect does not exist in IDX, the mean of stock trading volume observed on Monday during April is lower than the rest of the months.